Kochanek ojczyzny czy kochanek Laury? Wokół kreacji tytułowego bohatera dramatu Juliusza Słowackiego "Zawisza Czarny" = Lover of the homeland or Laura's lover? Around the creation of the title character of "Zawisza the Black" by Juliusz Słowacki - Rawski, Jakub (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
This article presents the literary creation of the title character "Zawisza the Black" ["Zawisza Czarny"] by Juliusz Słowacki. It is important to define the roles which Zawisza plays - he appears as a knight, a defender of the Commonwealth - "lover of the homeland", and Laura's lover.
Keywords: Słowacki, Juliusz (1809-1849); Zawisza Czarny; rycerz; kochanek; bohater romantyczny; Zawisza the Black; knight; lover; romantic hero